Damage Analysis of Grinding Machine Using FMEA and LTA Method at PT. X - Hidayah, Asfarina (TRANSMISI, 2023)
PT. X is a company in Banyuwangi, East Java, that produces shrimp feed. PT. X which is engaged in the shrimp feed production process has its own production machine that supports the shrimp feed production process. PT. X is able to carry out the production process from raw materials to finished materials, namely various shrimp feeds. One of the production machines at PT. X is a vertical pulvalizer grinding machine branded yeong-ming.  The objectives of this study are a. Analyze the breakdown of grinding machines using FMEA. b. Determine and categorize damage priorities using LTA. The method used in this study is the FMEA Method is carried out to identify grinding machine spare parts that are often damaged or aim to find out critical spare parts, with the FMEA table producing RPN values to rank the level of damage to grinding machine spare parts . There are 11 failures or failure modes obtained from grinding machine spare parts. Based on FMEA calculations, there is the highest RPN with a value of 108 resulting from the types of spare parts block C6 and block C7 with a failure cause of surface wear. These problems include failures in the operating process, where spare parts block C6 and block C7 function to smooth raw materials, where spare parts rub all the time with raw materials. Analysis using the LTA method on 11 causes of damage, there are 6 that are included in the category of outage problems (B), there are 4 that are included in the category of hidden failure (D) and outage problems (B) and there are 1 that are included in the category of safety problems (A) and outage problems (B).